Structural performance of a steel cable-stayed bridge under blast loading considering different stay patterns. (15th September 2020) - Tetougueni, Cyrille Denis; Zampieri, Paolo; Pellegrino, Carlo
Highlights: The structural performance of a Cable-stayed bridge has been studied. Fan patterns present a better stay configuration for displacement, strain, and stress amongst the three configurations. Cable loss is mainly due to the excessive tension stress in the cable or the breaking of the deck. Fan configuration is the most rigid configuration between the three displaying a controlled displacement after a blast event. Abstract: Accidental or extreme events can induce abnormal loads on structures contributing to a local damage of primary components or to the progressive collapse of the structure. Although hazards, which are usually difficult to be predicted, increase the complexity in the design, the need to determine the consequences on structures of these extreme events remains significant. This study aims to evaluate the damage induced by an accidental load such as blast loading to a cable-stayed bridge. In the first part of the paper, through non-linear dynamic analyses, it was possible to evaluate the structural response of three configurations of cable-stayed bridges, then to figure out the possible immediate and forthcoming damages considering different loading parameters and position. Finally, a displacement-controlled static non-linear pushover analysis of the structure has been performed to evaluate the limit state of the structure for a random position of blast loading and to predict the possible damage state during an accidental event such as blast loading. The results indicate significant effects of the structural configuration of the bridge and stay patterns. The Fan cable-stayed bridge is found to be the most effective among the considered configurations in reducing the dynamic effect induced by the blast loading on the structure. In addition, the deck is found to be less critical in terms of blast load mitigation close to the abutment and the pylon.